Analisis Keberhasilan Implementasi Sistem Coretax pada Perguruan Tinggi Negeri Berbadan Hukum : Studi pada Universitas Negeri Surabaya - Rizki Nur Amelia Bastian; Mulya Nofita Rahmi; Hariyati Hariyati; Eni Wuryani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The digital transformation of tax administration through the implementation of the Coretax system requires organizational readiness and qualified human resources to ensure effective system performance, particularly in State Universities with Legal Entity Status (PTN BH), which face complex tax management processes. This study aims to analyze the influence of managerial roles and human capital on the successful implementation of the Coretax system in PTN BH. A quantitative approach was employed using a survey method involving lecturers and administrative staff who utilize the Coretax system. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that human capital has a positive and significant effect on the success of Coretax implementation, with a path coefficient of 0.578 and a significance value of 0.000. Managerial role also has a positive and significant effect on the success of Coretax implementation, with a path coefficient of 0.174 and a significance value of 0.017. Furthermore, the R-square value of 0.486 demonstrates that both variables explain 48.6% of the variance in implementation success. The findings suggest that human capital is the most influential factor in supporting successful system implementation, while managerial support serves as a reinforcing factor in the digital transformation process. Therefore, PTN BH should strengthen users’ competencies, digital literacy, and tax knowledge while enhancing managerial commitment to optimize the sustainable implementation of the Coretax system.